Modification of growth conditions by mm-waves of wood-decaying mushroom’s cultures - I. A. Avagyan (ՀՀ ԳԱԱ հրատ.)
Basidial macromycetes are not only value food, but can be used as source of such biological active compounds as the genistein, β -glucans, glioxal–oxidase et al. In this work we used different frequencies of extremely high frequency of electromagnetic irradiation (EHF EMI) with the aim of obtaining mushroom cultures with increased fermentative activity by the modulation of its growth conditions during growth on the peptone media. We investigated the influence of the non-thermal extremely high frequency electromagnetic waves in the interval of 45-53 GHz on β-glucosidase activities of two species of wood-decaying mushroom. Բազիդիալ մակրոմիցետները օժտված են ոչ միայն բարձր սննդային հատկություններով, այլ նաև ծառայում են որպես արժեքավոր հումք այնպիսի կենսաակտիվ միացությունների համար, ինչպիսիք են գինեստին β-գլյուկանները, գլիոկսալ-օկսիդազը և այլն: Աշխատանքում օգտագործվել են գերբարձր հաճախությունների էլեկտրամագնիսական ճառագայթների տարբեր հաճախություններ՝ նպատակ ունենալով ստանալ սնկերի կուլտուրաներ (մշակույթներ), օժտված ավելի բարձր ֆերմենտային ակտիվությամբ, փոփոխելով միցելիումի աճի ընթացքում պեպտոնային միջավայրում պայմանները: Ուսումնասիրված է ոչ ջերմային գերբարձր հաճախությամբ էլեկտրամագնիսական ճառագայթման ազդեցությունը 45 ԳՀց – 53 ԳՀց միջակայքում երկու տեսակի փայտ քայքայող սնկերի β- գլյուկոզիդազ ֆերմենտի ակտիվության վրա: Базидиальные макромицеты обладают не только большой питательной ценностью, но служат также источником таких биологически активных соединений как гинестин, β- глюканы, глиоксаль-оксидазы и др. В работе были использованы различные частоты крайне высоких частот электромагнитного излучения с целью получения культуры грибов с повышенной активностью ферментов, модулируя условия выращивания в течении роста мицелия на пептонной среде. Исследовано воздействие нетепловых крайне высокочастотных электромагнитных волн в интервале 45-53 ГГц на активность β-глюкозидаз двух видов дереворазрушающих грибов.
Keywords: Biology; Botany; Mycology